Evaluation of Antioxidant and Antistress Effects of Essential Oils (Phyto-Plus) Supplementation in Broiler Chickens - Eldeib , Mahmoud, K.; AbdAllah, Hoda M.L.; Hamed, Abd-Allah S.; Mohamedy, Sahar, N.; AbdElall, Magda, N.A.; Ismail, EmanI. M. (International Journal of Poultry Science, 2021)
Objective: This study was conducted to evaluate the effect of thyme, oregano, peppermint, garlic, and rosemary combination (Phyto-plus) on the growth performance of broiler chickens in addition to their potential to be used as antistress and antioxidant. Materials and Methods: A total of 180 broiler chicks were divided into three equal groups with three replicates in each group: group1 (GP1) was served as a control given normal diet without any supplement. Group 2 (GP2) and group 3 (GP3) were supplemented with phyto-plus at doses of 100 and 400 g t–1 of ration respectively for 6 weeks. At the end of the 3rd and 6th week of experiment, live body weight and body weight gain of broiler chickens were calculated. Blood samples were taken to determine the levels of heat shock protein 70 (HSP70) and corticosterone hormone, in addition to enzymatic activity of superoxide dismutase (SOD), glutathione peroxidase (GST PX), catalase (CAT) and malondialdehyde (MDA). Side effects of phyto-plus were detected by estimation of liver and kidney markers. The histopathological examination of the liver, kidney and intestine were recorded. Results: The present data revealed improved growth performance and intestinal histomorphology in both two treated groups (GP2 and GP3) of broiler chickens, which were more pronounced with low dose than high dose of phyto-plus treated groups. There were a significant elevation in the level of HSP70, superoxide dismutase (SOD), glutathione peroxidase (GST PX) and catalase (CAT), while decreasing levels of corticosterone was detected with two doses of phyto-plus. No clinically significant elevation in liver and kidney markers (AST, ALT, Uric acid and creatinine) were seen as well as there were a normal liver and kidney pictures in broiler chickens given the low dose of phyto-plus. Conclusion: The low dose of phyto-plus (100 g t–1 of ration) was an optimum supplementation dose compared to the high dose (400 g t–1 of ration).